Purpura fulminans following immediate bilateral breast reconstruction: A case report and literature review - Matthew R. Zeiderman; Lauren M. Perry; Anthony N. Almazan; David G. Greenhalgh; Tina L. Palmieri (Elsevier, 2019)
Purpura fulminans (PF) is a rare, rapidly-progressive and life-threatening syndrome characterized by hypercoagulability that results in disseminated intravascular coagulation, microvascular thrombosis, and hemorrhagic infarction of the skin. Acute bacterial infection is the predominant etiology. The pathophysiology of PF results in extensive soft tissue necrosis with cutaneous wound depth mimicking full-thickness burns, limb gangrene requiring amputation, and multi-organ dysfunction syndrome. Consequently, mortality rate is over 50%. In the following case report, we present PF secondary to a complication of implant-based breast reconstruction following mastectomy. We review the management of PF and emphasize the importance of multidisciplinary management of this life-threatening illness.